Approaches to reduce zinc and iron deficits in food systems - Gregory, Peter J.; Wahbi, Ammar; Adu-Gyamfi, Joseph; Heiling, Maria; Gruber, Roman; Joy, Edward J.M.; Broadley, Martin R. (Elsevier, 2017)
There is a deficit of mineral micronutrients in global food systems, known as ‘hidden hunger’, especially in the global south. This review focuses on zinc (Zn) and iron (Fe), whose entry into food systems depends primarily on soil and crop factors. Approaches to increase dietary supplies of Zn and Fe include: (1) supplementation, (2) food fortification, (3) dietary diversification, and (4) crop biofortification, including breeding and fertilizer-based approaches. Supply-based estimates indicate that Zn deficiency might be more widespread than Fe deficiency in sub-Saharan Africa, although there are major knowledge gaps at an individual biomarker level. Recent analytical advances, including the use of stable isotopes of Zn and Fe, can play an increasing role in improving our understanding of the movement of micronutrients in food systems, and thereby help to reduce the immense human cost of ‘hidden hunger’.